If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 84 = 1x + 96 Reorder the terms: 84 = 96 + 1x Solving 84 = 96 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 84 + -1x = 96 + 1x + -1x Combine like terms: 1x + -1x = 0 84 + -1x = 96 + 0 84 + -1x = 96 Add '-84' to each side of the equation. 84 + -84 + -1x = 96 + -84 Combine like terms: 84 + -84 = 0 0 + -1x = 96 + -84 -1x = 96 + -84 Combine like terms: 96 + -84 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| 26z+9+11+-17z=-16+9 | | 17x-8=7x+2 | | (4/p)+(5/2)=7/p | | 22,45:0,345= | | 2/3*2/5= | | 100=10b+3g+50-.5b-.5g | | (5y-1)(5+y)=0 | | 3(4z-3)-3(2-2z)=6 | | x/9=3/2 | | 10,000^5/4 | | 5m+4*(m-4)= | | 18x^2-59x=-34 | | 5m+4(m-4)= | | 3x+30=24x-120 | | 3-1/2x=-2 | | 7x+x+8-2x+5=45 | | 6y+y+5y= | | 3xa-4xb+5xa-3xb= | | 2(4x-3)=10 | | 9x+237=4x+172 | | 4(y-2)-9=-7(-2y+5)-2y | | 11-w/2=60 | | 4x(5x+7)= | | ax^2+6ax+9a=0 | | -x+15-3x+6=-7x-4x | | (25.12^2)/(4(3.14)) | | -6/7x+17=-61 | | 7/9-5/13 | | (78x-48y)-(68x+28y)= | | -x+5y-3x-2y= | | 4(5y+7z)-28z= | | 5/13+6/11 |